Fenomenologis Peran Industri Rokok dalam Memberdayakan Kaum Perempuan (Studi Kasus Pabrik Rokok Tunas Mandiri, Pacitan, Jawa Timur) - Purwati Purwati; Lucky Nugroho; Zulfahmi Zulfahmi (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
The cigarette industry is an industry that has an important role in the economy and employment. The objectives of this research are (i) to determine the share of female workers compared to male workers at the Tunas Mandiri Cigarette Factory; (ii) To find out the benefits obtained by female workers in helping their household economy. The method used is a qualitative method supported by primary data, namely sourced from interviews. The results of this research are (i) The share of workers at the Tunas Mandiri Cigarette Factory, female workers, is greater than male workers, in 2023, namely the share of female workers will reach 95.4% and the share of male workers 4.6%; (ii) Women workers receive various benefits that are useful in helping their household economy, namely for school fees, for paying motorbike loans, for paying bank installments, for saving, for daily food costs. The implication of this research is to provide information and references that women can help their household economy by working in various industrial sectors.